Cerium conversion coating and sol-gel coating for corrosion protection of the WE43 Mg alloy - Pereira, Gualter Silva; Ramirez, Oscar Mauricio Prada; Avila, Pedro Renato Tavares; Avila, Julian Arnaldo [UNESP]; Pinto, Haroldo Cavalcanti; Miyazaki, Marcos Hideki; Melo, Hercílio Gomes de; Bose Filho, Waldek Wladimir (Elsevier, 2022)
In this work, the electrochemical behavior and morphological characterization of a system consisting of a cerium conversion layer, a hybrid sol-gel coating, and the two coatings applied sequentially (duplex) have been evaluated for the corrosion protection of WE43 Mg alloy. The different characterization techniques showed that the surface coverage by the hybrid coating was improved by the previous application of the conversion coating. The fitting of the impedance diagrams with electrical equivalent circuits allowed to propose a physical model for the coating, evidencing its interaction with the porous Mg oxide/hydroxide layer. Self-healing properties of the duplex coating were also disclosed.
Keywords: Ce conversion coating; Corrosion protection; Hybrid sol-gel coating; LEIM; Magnesium alloy